2014
DOI: 10.1242/jeb.106849
|View full text |Cite
|
Sign up to set email alerts
|

A context-dependent alarm signal in the antTemnothorax rugatulus

Abstract: Because collective cognition emerges from local signaling among group members, deciphering communication systems is crucial to understanding the underlying mechanisms. Alarm signals are widespread in the social insects and can elicit a variety of behavioral responses to danger, but the functional plasticity of these signals has not been well studied. Here we report an alarm pheromone in the ant Temnothorax rugatulus that elicits two different behaviors depending on context. When an ant was tethered inside an u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
41
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 54 publications
1
41
0
2
Order By: Relevance
“…Alarm pheromones are a common class of pheromones, which elicit defensive and escape behavior in social insects (Maschwitz 1964; Blum 1969). The nature of the response in any individual depends upon its caste and the context in which the alarm pheromone is presented (Maschwitz 1966; Shorey 1973; Sasaki et al 2014). At or near the colony, alarm pheromones elicit defensive behaviors, especially among specialized guard castes (Wilson 1965; Maschwitz 1966; Blum 1969; Sasaki et al 2014).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Alarm pheromones are a common class of pheromones, which elicit defensive and escape behavior in social insects (Maschwitz 1964; Blum 1969). The nature of the response in any individual depends upon its caste and the context in which the alarm pheromone is presented (Maschwitz 1966; Shorey 1973; Sasaki et al 2014). At or near the colony, alarm pheromones elicit defensive behaviors, especially among specialized guard castes (Wilson 1965; Maschwitz 1966; Blum 1969; Sasaki et al 2014).…”
mentioning
confidence: 99%
“…The nature of the response in any individual depends upon its caste and the context in which the alarm pheromone is presented (Maschwitz 1966; Shorey 1973; Sasaki et al 2014). At or near the colony, alarm pheromones elicit defensive behaviors, especially among specialized guard castes (Wilson 1965; Maschwitz 1966; Blum 1969; Sasaki et al 2014). Classically, honeybees sacrifice themselves in colony defense against mammals through stinging and subsequently eviscerating themselves to defend the colony (Hermann 1971).…”
mentioning
confidence: 99%
“…In cases where she was tethered and the colony selected an alternate nest, tandem leaders continued to put their efforts in releasing her. In T. rugatulus alarm pheromone released by the tethered individual repels the selection of that site (Sasaki et al, 2014). We found that there was no significant difference between the number of times the site containing the tethered gamergate and free gamergate were chosen as the final nest.…”
Section: Discussionmentioning
confidence: 64%
“…In T. rugatulus alarm pheromone released by the tethered individual repels the selection of that site (Sasaki et al, 2014). In cases where she was tethered and the colony selected an alternate nest, tandem leaders continued to put their efforts in releasing her.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals may switch tasks because all of the work in the first task is now completed. Alternatively, signals or cues in other modalities could cause individuals to switch to a task that has higher demand (Sasaki et al 2014;Vander Meer et al 1998). Individuals may even interrupt a current task to assess the need of the colony, as seen in honeybees (Johnson 2008(Johnson , 2009); or they may be spontaneously ending tasks, as seen in T. albipennis individuals when building (Franks and Deneubourg 1997), to wander inside the nest to assess demand for other tasks.…”
Section: Figurementioning
confidence: 99%